ANALISIS SISTEM PENENTUAN BESARAN NISBAH BAGI HASIL PADA PRODUK DEPOSITO DI BANK MUAMALAT INDONESIA KCP SITUBONDO - Ummal Khoiriyah (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2019)
Bank Muamalat Indonesia branch office Situbondo has a system for determining the amount of profit sharing ratio in deposit products with terms and conditions of deposits involved of depositing and refunding, bookkeeping, profit sharing, deposit termination, in line with applicable law and jurisdiction. Based on the results of the research, the system of determining the amount of profit sharing ratio on deposit products at Bank Muamalat Indonesia brach office Situbondo uses revenue sharing method. The method is still running in the application of profit sharing to customers which calculated based on the respective portion between depositors and bank. Characteristics of deposit products with the concept of profit sharing at Bank Muamalat Indonesia branch office Situbondo is the percentage ratio, for profit and for loss, collateral, determine the amount of ratio, how to resolve losses.